Implementation of The Local Budget Social Assistance Policy for Disability In Tangerang Selatan - Lisa Amilia; Retnowati WD Tuti (Universitas Muhammadiyah Gorontalo, 2021)
Social assistance is one of the poverty reduction programs carried out by the South Tangerang City Government. Poverty is defined as a condition of the inability of income to meet basic needs so that it is not able to guarantee survival. South Tangerang City has received the spill over effect of various economic impacts. Persons with disabilities have a low level of welfare. The low welfare is partly because they have limited physical functions and often have negative emotional experiences due to their physical limitations. Limited physical functions make it difficult for persons with disabilities to access work because they are considered less productive. This has a negative impact on persons with disabilities such as losing their role, independence, status, and financial stability. The purpose of this study is to analyze the implementation of regional budget social assistance policies for disabilities in South Tangerang. And to find out the supporting factors and inhibiting factors. This research method uses a qualitative approach with descriptive methods. qualitative approach, using the Theory of Policy Implementation according to Edward III. The results of this study indicate that the implementation of the Regional Budget Social Assistance Policy for Disabilities in South Tangerang has not been going well, it is based on poor communication from the implementor to the community, in terms of both human and financial resources are still lacking. Likewise, the supporting facilities in implementing social assistance for disabilities. And most importantly.